Unemployment and Output Growth: Evidence from Upper-Middle-Income Countries in Sub-Saharan Africa - Abraham, Ihensekhien Orobosa; Nosa, Aisien Leonard (American Economic & Social Review, 2018)
Several studies have found a negative relationship between unemployment rate and output growth rate. But such has not been ascertained concerning upper middle-income countries in Sub-Saharan Africa (SSA). Hence this paper examined this relationship using Panel Least Squares and Ordinary Least Squares estimation techniques based on annual series data from 1991 to 2017. The paper observed that the average output growth rate for upper middle-income countries in SSA in the period of the study was 6.36% while that of the unemployment average rate was 15.87%. The results of the panel Least Squares estimation reveals the existence of negative relationships between unemployment rate and output growth rate. In the country specific study, results from Botswana, Gabon, Mauritius and South Africa shows a positive relationship between unemployment and output growth rates revealing a case of non-inclusive growth. However, Equatorial Guinea and Namibia data on unemployment and output growth had negative relationships. The counter factual analyses conducted on the unemployment variable in term of some percentage reduction indicated that as more persons are employed there will be an increase in output growth. The findings, therefore suggests that the government should create more jobs based on labour intensive industries in upper middle-income countries in SSA, that the ratio of output growth needed to maintain stable level of unemployment rate could be sustained when there are boost in economic activities. Countries in upper middle-income in SSA that exhibited positive relationship between unemployment rate and output growth rate should concentrate more on how to increase the level of output growth rate through the boost in economic activities. Governments of these upper middle-income countries should have good policy mix focused on the reduction of unemployment at all levels.